Interaction of mid-latitude systems in the southern Hemisphere with southwest monsoon - KUMAR, S. (MAUSAM, 1992)
The movement of cold fronts with associated westerly waves in the lower troposphere across southern Africa and adjoining southwest Indian Ocean during the months of May to August for the years 1977 to 1981 has been examined in relation to the chief features of southwest monsoon. The deep frontal systems which penetrate north or latitude 25° S cause considerable fluctuations in the intensity of south to north pressure ridge along the east coast of southern Africa and Mascarene high. During the period of movement deep frontal systems from the west coast of South Africa to the Mozambique channel, the pressure index falls leading to decrease in cross equatorial flow. With further eastward movement of the system across Mozambique channel the pressure .index rises and causes increase in cross equatorial flow in Arabian Sea, strengthening equatorial westerlies and .increase in horizontal shear. The study has revealed a definite association between variation of pressure index with onset and various phases of the monsoon circulation. This association could be of help in understanding and forecasting of these monsoon features.